Incidence and clinical presentation of primary hemophagocytic lymphohistiocytosis in Sweden. Issue 2 (8th November 2014) - Meeths, Marie; Horne, AnnaCarin; Sabel, Magnus; Bryceson, Yenan T.; Henter, Jan‐Inge
<x xml:space="preserve">Abstract</x> Background Primary hemophagocytic lymphohistiocytosis (HLH) represents a group of inherited hyperinflammatory immunodeficiencies, including familial HLH (FHL), Griscelli syndrome type 2 (GS2), and X‐linked lymphoproliferative syndrome (XLP). We previously reported an annual incidence of suspected primary HLH in Sweden 1971–1986 of 0.12 per 100, 000 children. Here, we determined if the incidence had increased with concomitant awareness. Procedure Children <15 years old presenting with HLH 1987–2006 in Sweden were identified through the national mortality registry as well as by nation‐wide inquiries to all pediatric centers. HLH was diagnosed according to the HLH‐2004 diagnostic guidelines (in case of missing data of at least three of the eight diagnostic criteria, fulfillment of four was sufficient for inclusion). We defined primary HLH as patients presenting with HLH requiring transplantation or dying of disease. Results Remarkably, the minimal annual incidence rate of primary HLH remained 0.12 per 100, 000 children, equating to 1.8 per 100, 000 live births. Notably, an increased overall survival was observed in 1997–2006, relative to the period 1987–1996. During the subsequent 5‐year period, 2007–2011, the incidence of genetically and/or functionally verified primary HLH was 0.15 per 100, 000 children per year, suggesting that new assays may aid the identification of patients with primary HLH. Conclusion The annual incidence of primary HLH in Sweden is 0.12–0.15 per 100, 000 children per year. Pediatr Blood Cancer 2015;62:346–352. © 2014 Wiley Periodicals, Inc.